Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming (Alan, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Po litics matters. Context too. And blueprints have limited value. Our st rategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...